2004
DOI: 10.1515/znb-2004-0610
|View full text |Cite
|
Sign up to set email alerts
|

Some Novel Amino Acid-Schiff Bases and their Complexes Synthesis, Characterization, Solid State Conductivity Behaviors and Potentiometric Studies

Abstract: Three new Schiff bases derived from the condensation reaction of thiophene-2-carbaldehyde and DL-alanine, DL-valine and DL-phenylalanine have been synthesized and their Co(II), Ni(II) and Cu(II) complexes have been prepared. The Schiff bases and the complexes have been characterized by their analytical and spectral data. The protonation constants of the Schiff bases and stability constants of the complexes have been determined potentiometrically in aqueous medium at 25 °C and 0.1 M KCl ionic strength. Solid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…The conditions which favorable the formation of amino acids Schiff base were described in some papers [9][10][11]. On the other hand, the formed organic amino acid Schiff bases are not stable and sensitive to moisture and decompose when exposed to air [12].…”
Section: Introductionmentioning
confidence: 99%
“…The conditions which favorable the formation of amino acids Schiff base were described in some papers [9][10][11]. On the other hand, the formed organic amino acid Schiff bases are not stable and sensitive to moisture and decompose when exposed to air [12].…”
Section: Introductionmentioning
confidence: 99%
“…All the synthesized compounds were found to be chiral [44]. The occurrence of E/Z isomerism at the imine band of the molecules was suggested by Sari and Gürkan [45].…”
Section: Resultsmentioning
confidence: 68%
“…X -1 cm 2 mol -1 . This state indicated that the 1:1 electrolytic behaviour for Cr(III) (Sari and Gürkan 2004). Zn(II) complexes were nonelectrolytic.…”
Section: Resultsmentioning
confidence: 90%